The Load Shifting Potential of Domestic Refrigerators in Smart Grids: A Comprehensive Review - Luís Sousa Rodrigues; Daniel Lemos Marques; Jorge Augusto Ferreira; Vítor António Ferreira Costa; Nelson Dias Martins; Fernando José Neto Da Silva (Energies, 2022)
Domestic refrigeration and freezing appliances can be used for electrical load shifting from peak to off-peak demand periods, thus allowing greater penetration of renewable energy sources (RES) and significantly contributing to the reduction of CO2 emissions. The full realization of this potential can be achieved with the synergistic combination of smart grid (SG) technologies and the application of phase-change materials (PCMs). Being permanently online, these ubiquitous appliances are available for the most advanced strategies of demand-side load management (DSLM), including real-time demand response (DR) and direct load control (DLC). PCMs are a very cost-effective means of significantly augmenting their cold storage capacity and, hence, their load-shifting capabilities. Yet, currently, refrigerators and freezers equipped with PCMs for DSLM are still absent in the market and research works focusing on the synergy of these technologies are still scarce. Intended for a multidisciplinary audience, this broad-scoped review surveys the literature to evaluate the technological feasibility, economic viability and global impact of this combination. The state-of-the-art of SG-enabling technologies is investigated—e.g., smart meters, Internet-of-Things (IoT)—as well as current and future standards and norms. The literature on the use of PCMs for latent heat/cold storage (LHCS) is also reviewed.